Nanotechnology as a Tool for Optimizing Topical Photoprotective Formulations Containing Buriti Oil (Mauritia flexuosa) and Dry Aloe vera Extracts: Stability and Cytotoxicity Evaluations - Maria Cristina Pinheiro Pereira Reis-Mansur; Christian Campos Firmino Gomes; Fiammetta Nigro; Eduardo Ricci-Júnior; Zaida Maria Faria de Freitas; Elisabete Pereira dos Santos (MDPI AG, 2023)
Human beings are actively exposed to ultraviolet (UV) radiation, which is associated with skin cancer. This has encouraged the continuous search for more effective and safer photoprotective formulations. Along with the application of traditional organic sunscreens, there is a growing interest in "green products" containing natural compounds such as plant extracts and oils. This trend is combined with the use of nanotechnology as a tool for optimizing the vehicles of such compounds. Nanoemulsions (NEs) are suitable for the encapsulation of natural compounds, which improves topical treatment. Therefore, we have developed oil-in-water (O/W) nanoemulsions containing 3% buriti oil (BO), incorporated in a 10% vegetal extract of Aloe vera (AV) by means of ultrasonic processing to improve the chemical characteristics of this component and, consequently, its efficacy and safety in pharmaceutical and cosmetic formulations. The composition of the formulation was initially defined in a preliminary study on surfactants where the concentrations of Tween® 80 and Span® 20 were evaluated in relation to particle size and the polydispersity index (PDI). The nanoemulsion was prepared and then chemical sunscreens were incorporated with the aim of developing a sunscreen nanoemulsion called NE-A19. This nanoemulsion was found to be the best formulation due to its stability, droplet size (146.80 ± 2.74), and PDI (0.302 ± 0.088), with a monomodal size distribution. The stability was evaluated over 90 days and showed a low growth in particle size at the end of the study. NE-A19 exhibited good viscosity and organoleptic properties, in addition to an occlusion factor indicating an interesting and higher water holding capacity when compared with a NE without AV (p < 0.05). The in vitro efficacy and safety studies of NE-19A were promising. Its average in vitro sun protection factor value was 49, with a critical wavelength (λc) of 369.7 nm, satisfactory UVA protection, and a UVA/UVB ratio of 0.40, indicating broad spectrum protection against UVA and UVB radiation. Furthermore, NE-19A displayed a good safety profile in dermal keratinocytes. It can be concluded that NE-19A is a promising formulation for carrying natural products, such as buriti oil and AV, associated with synthetic filters in lower concentrations.